Evaluation of the sanitation aspects in the manufacture of "TAHO" - a case study - Matta, Julie Pearl S.
This study was conducted to investigate on the sanitation aspects of the manufacture of "taho". It was divided into two phases. Phase I, dealt with the assessment of the manufacturing plant's sanitation and personnel hygiene. An interview schedule was used to provide the manufacturing establishment. This was followed by the assessment of the plant sanitation and personnel hygiene through actual observations and microbiological tests. Results showed that sanitation and personnel hygiene did not meet the minimum sanitary indices. This was confirmed by the observed neglect of requirements for personnel hygiene. There was also the absence of proper manufacturing and sanitizing practices observed. In this connection, the researcher made some in-depth analysis of the process floe and operations as they relate to sanitation. Product quality based on microbiological assessment and sensory evaluation were done. Contradictory to the researchers expectations, the product was found to be safe for consumption when freshly made. In fact, based on panelists' reactions. they were considered to have very pleasing sensory attributes. However, because of the conditions in the environment, it may be expected that product shelf-life would be short. Furthermore, analysis of the process showed potentials for process optimization. There were steps in the operation which could still be improved. On the basis of the results, the researcher proposed a sanitation which was designed to help the manufacturing establishment (a) in the improvement of the total process to reduce handling, and (b) reduce potential for contamination.